Prognostic Significance of Frontal QRS-T Angle in Patients with Idiopathic Dilated Cardiomyopathy - Sheng-Na Li; Xin-Lin Zhang; Guo-Long Cai; Ruo-Wei Lin; He Jiang; Jian-Zhou Chen; Biao Xu; Wei Huang (Chinese Medical Journal, 2016)
Background: Current risk stratification of idiopathic dilated cardiomyopathy (IDC) lacks sufficient sensitivity and specificity. The objective of this study was to investigate the predictive role of frontal QRS-T angles in IDC. Methods: A prospective study with 509 IDC patients was performed from February 2008 to December 2013 in the Affiliated Drum Tower Hospital, Nanjing University School of Medicine. Baseline values and changes in QRS-T angles were recorded. Follow-up was conducted every 6 months. Analyses by Cox Proportional Hazards model were performed to evaluate the association between QRS-T angle and outcomes. The primary outcome of interest was all-cause mortality. Results: During a median follow-up of 34 months, 90 of 316 patients with QRS-T angles >90° died compared to 31 of 193 patients with QRS-T angles ≤90° (hazard ratio [HR] =2.4, P < 0.001). Cardiac death was more prevalent in patients with a wide QRS-T angle (HR = 2.4, P < 0.001), similar to heart failure rehospitalization (HR = 2.5, P < 0.001). After adjustment for potential prognostic factors, the QRS-T angle was independently associated with all-cause mortality (HR = 2.5, P < 0.05), cardiac mortality (HR = 1.9, P < 0. 05), and heart failure rehospitalization (HR = 2.3, P < 0.01). Optimized therapy significantly narrowed the frontal QRS-T angle (100.9 ± 53.4° vs. 107.2 ± 54.4°, P < 0.001). The frontal QRS-T angle correlated well with established risk factors, such as left ventricular ejection fraction, brain natriuretic peptide, and New York Heart Association functional class. Conclusions: The frontal QRS-T angle is a powerful predictor of all-cause mortality, cardiac mortality, and worsening heart failure in IDC patients, independent of well-established prognostic factors. Optimized therapy significantly narrows the QRS-T angle, which might be an indicator of medication compliance, but this requires further investigation.